Exploring the efficacy of short-term high intensity interval training (HIIT) for improving surgical risk factors in older adults - Blackwell, James E.M. (2019)
Purpose: National cancer waiting time guidelines enforce a limited time period between diagnosis and surgery (31 days). Low preoperative cardiorespiratory fitness (CRF), in particular anaerobic threshold (VO2AT), is associated with poorer surgical outcomes. The optimal preoperative exercise regimes to improve cardiorespiratory fitness (CRF) are not fully understood. High intensity interval training (HIIT) may represent an efficacious means of increasing CRF in a short time period. The effect of advancing age and comorbidity, in relation to the optimal HIIT regime to evoke positive responses are unknown. Methods: Systematic review and meta-analyses established that HIIT is more efficacious than moderate continuous exercise, particularly in patients with cardiac pathology, over truncated timeframes. Our 5 x 1 minute (90 seconds rest periods between) HIIT protocol is used throughout studies in this thesis. Cardiopulmonary exercise testing provides objective measurement of CRF parameters. Results: HIIT confers greater improvements in CRF over short periods in individuals with chronic disease versus moderate continuous training (MCT). Our HIIT protocol delivers improvements in VO2AT (mean difference (MD)) over short periods (<31 days) in healthy sedentary (MD 2.95 ml/kg/min), comorbid octogenarians (MD 1.21 ml/kg/min) and urological cancer patients (MD 2.26 ml/kg/min). Conclusions: Short term HIIT is more efficacious than MCT in cardiac patients. Supervised HIIT delivers greater improvements in CRF than work matched unsupervised HIIT. Certain elderly individuals with comorbidity are able to rapidly improve CRF following HIIT. Preoperative HIIT is efficacious, safe and feasibly delivered within the current clinical framework within urology.